From Free Access to (Fee) Low Cost, Access Based: A Survey of HINARI in Nigeria. Issue 2 (3rd April 2019) - Olayemi, Olalekan Moses; Abolarinwa, Shola Timothy
Abstract: This study focused on the change in status of Nigeria from HINARI free access to (fee) low cost, access based. A mixed method research design incorporating qualitative and quantitative approaches was used for the study. Questionnaires and interviews were used as the instrument for data collection. The findings of the study revealed most of the respondents affirmed to be conversant with HINARI and acknowledged the resources within are relevant to their institutions and users. Also, according to the study, the majority of respondents said they were aware that Nigeria had been moved from free access to low cost, access based. However, most respondents said their institutions have been unable to subscribe since the introduction of fee due to lack of funds. This study recommends that creative thinking and innovation be employed to identify alternative sources of funding and that government should increase the subvention allocated to libraries and release these funds when due.